PENGOLAHAN NANOSILIKA DAUN BAMBU ANTI ORGANISME PENGGANGGU TANAMAN SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT DI GAMPONG MEURANDEH KOTA LANGSA, ACEH - Zulfan - Arico; Sri Jayanthi; Yulina Ismida; Nuraini Nuraini (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2019)
The level of income in the City of Aceh Province, especially in Gampong Meurandeh is still relatively low. One reason is the use of free time for non-productive housewives. The purpose of this activity is to improve the ability of housewives to produce high economic value products by utilizing their free time by utilizing available natural resources, one of which is bamboo plants to be able to increase the family's economic income. The method used in the implementation of the activities carried out jointly with the mothers in Gampong meurandeh Langsa Lama Subdistrict, Langsa City is by (1) Socialization, implementation, survey and assistance programme. The current activity has been completed and has produced the superior bipesticide product of the community of Meurandeh Village. The conclusions that can be obtained from the implementation of the program are (a) The high level of participation from the community service program partners has a positive impact on the implementation of the program, seen from training and assistance in making products, (b) The program is able to produce alamai biopesticides made from bamboo leaf nanosilica so that it can improve the economy of the community and the product is environmentally friendly so that it can maintain environmental sustainability. Suggestion, (c) The high interest and enthusiasm of the community in participating in the Community Service program is expected to get special attention, so the program will continue. Keywords: Nanosilica, Bamboo Leaves, Meurandeh Village